5-Demethylnobiletin mediates cell cycle arrest and apoptosis via the ERK1/2/AKT/STAT3 signaling pathways in glioblastoma cells - Zhang, Xuehua; Zhao, Leilei; Xiao, Jinlong; Wang, Yudi; Li, Yunmeng; Zhu, Chaoqun; Zhang, He; Zhang, Yurui; Zhu, Xiao; Dong, Yucui (Frontiers in Oncology, 2023)
5-Demethylnobiletin is the active ingredient in citrus polymethoxyflavones that could inhibit the proliferation of several tumor cells. However, the anti-tumor effect of 5-Demethylnobiletin on glioblastoma and the underlying molecular mechanisms are remains unknown. In our study, 5-Demethylnobiletin markedly inhibited the viability, migration and invasion of glioblastoma U87-MG, A172 and U251 cells. Further research revealed that 5-Demethylnobiletin induces cell cycle arrest at the G0/G1 phase in glioblastoma cells by downregulating Cyclin D1 and CDK6 expression levels. Furthermore, 5-Demethylnobiletin significantly induced glioblastoma cells apoptosis by upregulating the protein levels of Bax and downregulating the protein level of Bcl-2, subsequently increasing the expression of cleaved caspase-3 and cleaved caspase-9. Mechanically, 5-Demethylnobiletin trigged G0/G1 phase arrest and apoptosis by inhibiting the ERK1/2, AKT and STAT3 signaling pathway. Furthermore, 5-demethylnobiletin inhibition of U87-MG cell growth was reproducible in vivo model. Therefore, 5-Demethylnobiletin is a promising bioactive agent that might be used as glioblastoma treatment drug.